Peran Bidang Pertanian dalam Pembangunan Wilayah Kabupaten Bener Meriah (Pendekatan Location Quotient dan Shift Share Analysis) - Meyranti, Risky; Rombeallo, Esra; Wahyuni, Dwi (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2025)
The agricultural sector plays a strategic role in supporting economic resilience. In Bener Meriah Regency, Aceh Province, agriculture serves as the main pillar of the economy, with the majority of the population working as farmers and possessing significant potential in the horticulture and plantation sub-sectors, particularly coffee. This study aims to analyze the role of the agricultural sector in regional development in Bener Meriah Regency, identify its status as a base sector, and determine leading commodities with development potential. The research uses secondary data from the BPS, the Agriculture and Plantation Office, the BAPPEDA, and other supporting literature. The analysis employs the Location Quotient (LQ) method to determine the base sector and Shift Share Analysis (SSA) to assess sector competitiveness and growth. The results show that the agricultural sector had an average LQ value of 1.80 during the 2013–2017 period, indicating it is a base sector with a production surplus that can be marketed outside the region. Positive Proportional Shift and Differential Shift values indicate significant growth at both the regency and provincial levels. Corn and coffee were identified as leading base commodities, with Gayo coffee having a high competitive advantage in both domestic and international markets. These findings highlight that strengthening the agricultural sector, through the development of leading commodities and sustainable management, can improve the welfare of the people in Bener Meriah Regency.